Political ideology and fiscal policy in Portugal: Minimal evidence of influence - Dias, P.; Leonardo, R. (Journal of Economic Policy Reform, 2025)
This study investigates the extent to which political ideology shapes fiscal and public spending policies in Portugal between 1990 and 2019. Drawing on seven fiscal and expenditure variables, we apply Cramer’s V Test to examine associations with government ideology. The analysis reveals that 28 of 35 associations are weak or very weak, with only a few moderate links emerging during the sovereign debt crisis. These results indicate that fiscal outcomes are primarily driven by external shocks, institutional frameworks, and international constraints, while political ideology plays only a minimal role in influencing policy directions.